Inorganic-organic Synergy in Nano-hybrids Makes a New Class of Drug with Targeted Delivery: Glutamate Functionalization of Iron Nanoparticles for Potential Bone Marrow Delivery and X-ray Dynamic Therapy - Ghosh, Ria; Mondal, Susmita; Mukherjee, Dipanjan; Adhikari, Aniruddha; Bhattacharyya, Maitree; Pal, Samir K. (Current Drug Delivery, 2022)
The direct delivery of therapeutic molecules is generally inefficient and has several problems. Hence, nanomedicines with targeted and controlled delivery applications have been an exciting field of research for the past decade. In this regard, the adjustable properties of inorganic nanoparticles like particle size distribution, ability to change the targeting ligand to have a higher affinity towards the pathologic cell, and controlled delivery properties have made them indispensable for targeted drug delivery applications. Changing the ligand on the surface of the inorganic nanoparticle can direct different therapeutic molecules to different organs like the liver, spleen, kidney, bone, and even brain. However, while the other targeted nanomedicines are well-reported, the targeting of therapeutics to bone marrow cells is sparse in the literature. Hence, the administration of therapeutics for bone-related disorders, like bone metastases, leads to several problems, such as severe systemic toxicity and suboptimal efficacy. In this direction, we have shown our successful effort to functionalise a model inorganic nanoparticle (Fe2O3) by glutamate ligand which is reported to have a high affinity towards the NMDA receptors of the bone cells. We have performed spectroscopic studies to characterize the nano-hybrid. We have shown that the cargo or the Fe2O3 nanoparticle possesses the ability to generate photo-induced reactive oxygen species (ROS), thereby leading to a therapeutic opportunity for bone metastases. In addition, the nanoparticle also possesses the ability to generate enhanced ROS on X-ray irradiation, which may provide a new strategy for bone metastases and cancer therapy. Also, this paper reviews the advancement in the drug delivery applications of inorganic nanoparticles and highlights the crosstalk between the inorganic nanoparticles with the conjugated targeting ligand for efficient delivery applications.
Keywords: nanoparticles